(untitled) (TSUL LEGAL REPORT, 2026)
This article describes the concept of the crime of failure to perform one’s duties properly, its specific features, and the subjective aspects of the crime. The subjective side of the crime of failure to perform one’s duties is analyzed based on the opinions of experts in criminal law. The author, employing a scientific approach to the perspectives of these scholars, illuminates his views through rigorous analysis. Additionally, the article states that representatives of various professions – including doctors, rescuers, builders, hairdressers, and electricians – are considered a special subject in this context. It reveals the signs of criminal negligence that may arise from a person’s actions when this crime is committed carelessly. The motives and goals underlying any activity a person consciously performs are also analyzed in relation to Article 116 of the Criminal Code, along with its specific features. The crime of improperly performing one’s duties within a professional context is discussed in terms of both subjective carelessness and intent. Furthermore, the article substantiates the need to separate the crime of improperly performing one’s duties from that of a medical worker into a distinct article and analyzes crime statistics related to the improper performance of duties across various professions for the years 2014-2022, as well as relevant judgments examined in connection with the research. The article also provides scientifically based conclusions and suggestions for improving legal norms that govern responsibility for the crime of improper performance of one’s duties.